2022
DOI: 10.18280/ijsdp.170716
|View full text |Cite
|
Sign up to set email alerts
|

The Work Commitment of Construction Project Managers in Indonesia Using the Structural Equation Modelling Method

Abstract: The aims of this research were to determine how much influence the independent variables have on the dependent variable and to identify the variable with the dominant influence on the dependent variable the work commitment of construction project managers. The independent variable is a variable that can affect the value of other variables. The dependent variable is influenced by the independent variable either directly or indirectly. After data collection, the research method used was data analysis using the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The signalling theory emphasizes that the supervisor's perceptions of green HR practices can significantly influence the job-related outcomes of their subordinate through the process and human capital advantage [64,65]. Additionally, as seen by the supervisor, good green HR practices indicate the employee's commitment to the business and its objectives [66][67][68], which predicts employee outcomes [69]. According to experts, managers can successfully translate green HR practices through transformational leadership.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The signalling theory emphasizes that the supervisor's perceptions of green HR practices can significantly influence the job-related outcomes of their subordinate through the process and human capital advantage [64,65]. Additionally, as seen by the supervisor, good green HR practices indicate the employee's commitment to the business and its objectives [66][67][68], which predicts employee outcomes [69]. According to experts, managers can successfully translate green HR practices through transformational leadership.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Several studies have shown that organizational resources (supervision at work (Bakker, Van Veldhoven, et al, 2010)) and social resources (social support (Ángeles López-Cabarcos et al, 2022)) influence work engagement through personal resources (self-esteem and self-efficacy beliefs). Thus, the presence of substantial organizational and social resources reinforces personal resources, which, in turn, strengthens job commitment (Sahadi et al, 2022).…”
Section: Conceptual Backgroundmentioning
confidence: 99%